Achados clínicos de afecções orais em bugios ruivos (Alouatta guariba clamitans) (Cabrera, 1940) - Dias Neto, Ramiro das Neves [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study was to investigate dental disorders of Brown howler monkeys (Alouatta guariba clamitans) maintained in captivity. The hypothesis is that the identification and diagnosis of the lesions may contribute to control and prevention. Sixteen intact red howler monkeys (Alouatta guariba clamitans), 8 females and 8 males, weighing from 3.9 to 6.8 kg were studied. Under general anesthesia, the teeth were evaluated by visual inspection, probing, palpation, and intraoral radiographic exam. The findings were registered on dental chart specific for primates. From the 16 monkeys evaluated in the present study, 88% (n=14) had some type of dental disorder. The lesions observed were dental calculus (88%), dental wear (81%), missing tooth (38%), gingivitis (19%), gingival recession (6%), dental fracture (19%), pulp exposition (19%), and dental staining (25%). Alouatta guariba clamitans maintained in captivity have high rate of dental problems

O objetivo deste estudo foi investigar problemas dentários de bugios-ruivos (Alouatta guariba clamitans) mantidos em cativeiro. A hipótese é que a identificação e diagnóstico das afecções podem contribuir para o controle e prevenção de lesões orais. Foram estudados dezesseis bugios-ruivos (Alouatta guariba clamitans), oito fêmeas e oito machos, pesando entre 3,9 a 6,8 quilogramas. Sob anestesia geral, a cavidade oral e os dentes foram avaliadas por inspeção visual, palpação, sondagem e exame radiográfico intraoral. Os resultados foram registrados em odontogramas específicos para primatas. Dos 16 primatas avaliados no presente estudo, 88% (n = 14) apresentaram algum tipo de distúrbio dental. As afecções observadas foram cálculo dentário (88%), desgaste dentário (81%), ausência dentária (38%), a gengivite (19%), retração gengival (6%), fratura dentária (19%), exposição de polpa (19%) e escurecimento dental (25%). Alouatta guariba clamitans mantidos em cativeiro têm alto índice de problemas dentários
Keywords: Guariba (Macaco); Dentes - Doenças - Tratamento; Tratamento dentario; Manifestações orais de doenças; Dental therapeutics